Temporal transcriptome analysis reveals several key pathways involve in cadmium stress response in Nicotiana tabacum L. - Li, Chenyang; Hong, Yi; Sun, Jinhao; Wang, Guoping; Zhou, Huina; Xu, Liangtao; Wang, Long; Xu, Guoyun (Frontiers in Plant Science, 2023)
Tobacco has a strong cadmium (Cd) enrichment capacity, meaning that it can absorb large quantities from the environment, but too much Cd will cause damage to the plant. It is not yet clear how the plant can dynamically respond to Cd stress. Here, we performed a temporal transcriptome analysis of tobacco roots under Cd treatment from 0 to 48 h. The number of differentially expressed genes (DEGs) was found to change significantly at 3 h of Cd treatment, which we used to define the early and middle stages of the Cd stress response. The gene ontology (GO) term analysis indicates that genes related to photosynthesis and fatty acid synthesis were enriched during the early phases of the stress response, and in the middle phase biological process related to metal ion transport, DNA damage repair, and metabolism were enriched. It was also found that plants use precursor mRNA (pre-mRNA) processes to first resist Cd stress, and with the increasing of Cd treatment time, the overlapped genes number of DEGs and DAS increased, suggesting the transcriptional levels and post-transcriptional level might influence each other. This study allowed us to better understand how plants dynamically respond to cadmium stress at the transcriptional and post-transcriptional levels and provided a reference for the screening of Cd-tolerant genes in the future.